An RNA polymerase II transcription factor has an associated DNA-dependent ATPase (dATPase) activity strongly stimulated by the TATA region of promoters. - Conaway, R C (1989)
A transcription factor required for synthesis of accurately initiated run-off transcripts by RNA polymerase II has been purified and shown to have an associated DNA-dependent ATPase (dATPase) activity that is strongly stimulated by the TATA region of promoters. This transcription factor, designated delta, was purified more than 3000-fold from extracts of crude rat liver nuclei and has a native molecular mass of approximately 230 kDa. DNA-dependent ATPase (dATPase) and transcription activities copurify when delta is analyzed by hydrophobic interaction and ion-exchange HPLC, arguing that transcription factor delta possesses an ATPase (dATPase) activity. ATPase (dATPase) is specific for adenine nucleotides; ATP and dATP, but not CTP, UTP, or GTP, are hydrolyzed. ATPase (dATPase) is stimulated by both double-stranded and single-stranded DNAs, including pUC18, ssM13, and poly(dT); however, DNA fragments containing the TATA region of either the adenovirus 2 major late or mouse interleukin 3 promoters stimulate ATPase as much as 10-fold more effectively than DNA fragments containing nonpromoter sequences. These data suggest the intriguing possibility that delta plays a critical role in the ATP (dATP)-dependent activation of run-off transcription through a direct interaction with the TATA region of promoters.